Is there an agreement between self-reported medical diagnosis in the CARTaGENE cohort and the Québec administrative health databases? - Yves Payette; Cristiano Soares de Moura; Catherine Boileau; Sasha Bernatsky; Nolwenn Noisel (International Journal of Population Data Science, 2020)
Background Population health studies often use existing databases that are not necessarily constituted for research purposes. The question arises as to whether different data sources such as in administrative health data (AHD) and self-report questionnaires are equivalent and lead to similar information.